Evaluating a Multidimensional Reading Comprehension Program and Reconsidering the Lowly Reputation of Tests of Near‐Transfer. Issue 1 (19th January 2018) - Fuchs, Douglas; Hendricks, Emma; Walsh, Meagan E.; Fuchs, Lynn S.; Gilbert, Jennifer K.; Zhang Tracy, Wen; Patton, Samuel; Davis‐Perkins, Nicole; Kim, Wooliya; Elleman, Amy M.; Peng, Peng
Abstract: We conducted a 14‐week experimental study of 2 versions of a relatively comprehensive RC intervention that involved 50 classroom teachers, 15 tutors, and 116 children drawn in equal proportions from grades 3 and 5 in 13 schools in a large urban school district. Students were randomly assigned in equal numbers to the two tutoring conditions and a control group. Results indicated that students in the two tutored groups tended to perform comparably on all tests and to outperform controls (more so in grade 5 than grade 3) on near‐transfer but not far‐transfer measures of RC. This differential pattern of program effects for near‐ versus far‐transfer measures raises questions about how tests of near‐transfer and far‐transfer are conventionally understood.